2015
DOI: 10.1007/s12020-015-0786-4
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hyperglycemia was ameliorated by taking metformin 30 min before a meal than taking metformin with a meal; a randomized, open-label, crossover pilot study

Abstract: Taking metformin with a meal has been shown to decrease bioavailability of metformin. We hypothesized that taking metformin 30 min before a meal improves glucose metabolism. As an animal model, 18 Zucker-rats were divided into three groups as follows: no medication (Control), metformin (600 mg/kg) with meal (Met), and metformin 10 min before meal (pre-Met). In addition, five diabetic patients were recruited and randomized to take metformin (1000 mg) either 30 min before a meal (pre-Met protocol) or with a meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…These findings are in agreement with those of our previous pre‐clinical study in which pre‐Met administration lowered plasma TG and glucose levels in mice. Furthermore, the present findings are consistent with a previous clinical study that showed lower glucose concentrations with pre‐Met administration before oral glucose tolerance testing. However, unlike the previous clinical study, we found that pre‐Met administration increased plasma glucose levels at t = 240 min with a delayed peak time compared with post‐Met administration.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those of our previous pre‐clinical study in which pre‐Met administration lowered plasma TG and glucose levels in mice. Furthermore, the present findings are consistent with a previous clinical study that showed lower glucose concentrations with pre‐Met administration before oral glucose tolerance testing. However, unlike the previous clinical study, we found that pre‐Met administration increased plasma glucose levels at t = 240 min with a delayed peak time compared with post‐Met administration.…”
Section: Discussionsupporting
confidence: 93%
“…However, post-meal administration of metformin is performed to maintain patients’ adherence in the clinical setting. A recent report revealed that postprandial glucose levels are improved by pre-meal administration of metformin compared with those following post-meal treatment [24]. Our data demonstrated that pre-meal treatment of metformin significantly improved both glucose and TG concentrations compared with post-meal administration (Figure 2C,E).…”
Section: Discussionsupporting
confidence: 64%
“…Metformin has been reported to suppress glucose spikes when taken prior to meals [ 25 ]. However, in the present study, metformin was not administered prior to the OGTT.…”
Section: Discussionmentioning
confidence: 99%